2010
DOI: 10.1128/jcm.00815-09
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Sudden Death Due to Myocarditis Caused by Adenovirus Serotype 3

Abstract: Myocarditis is a rare cause of sudden death in childhood. We describe the sudden death of a child from viral myocarditis, which we demonstrate was likely caused by an uncontrolled inflammatory response to a disseminated adenovirus serotype 3 infection originating in the tonsil. CASE REPORTAn 11-year old boy collapsed suddenly at home. He was transferred to a hospital by ambulance. Cardiopulmonary resuscitation was unsuccessful, and he was pronounced dead. He had visited his general practitioner (GP) 1 day earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
(16 reference statements)
2
24
0
Order By: Relevance
“…CD3 ϩ T cells and F4/80 ϩ macrophages were recruited to the hearts of neonatal mice after MAV-1 infection. This is consistent with observations that hearts of patients with HAdV myocarditis are infiltrated with T cells and macrophages (34,37). The T cell infiltrates following MAV-1 infection were mainly CD8 ϩ T cells, although CD4 ϩ T cells were also present.…”
Section: Discussionsupporting
confidence: 91%
“…CD3 ϩ T cells and F4/80 ϩ macrophages were recruited to the hearts of neonatal mice after MAV-1 infection. This is consistent with observations that hearts of patients with HAdV myocarditis are infiltrated with T cells and macrophages (34,37). The T cell infiltrates following MAV-1 infection were mainly CD8 ϩ T cells, although CD4 ϩ T cells were also present.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies showed that types 1, 2, 3, 5 and 21 are associated with myocarditis in children [16]. Fatal cases of HAdV-3 myocarditis have been reported by Treacy et al [15]. Adenovirus type-3 was identified as the causative agent of LRTI and suspected myocarditis in the current study.…”
Section: Discussionsupporting
confidence: 64%
“…Several earlier reports have documented the association of HAdV-3 with conjunctivitis, pharyngitis and gastrointestinal symptoms in children and adolescents and also with fatal pneumonia and myocarditis. 10,31,32 The frequency of detection of HAdV-7 increased to 25% from 5.6% in the previous two years of surveillance efforts in Kansas City. HAdV-7 infections in children were associated with severe illness such as acute bronchiolitis (54.4%) and pneumonia (44.4%).…”
Section: Variablesmentioning
confidence: 98%
“…9 Recently, a sudden death of a child from myocarditis was reported due to an uncontrolled inflammatory response to a disseminated adenovirus serotype 3 infection in the UK. 10 Sequences of hypervariable regions of hexon gene provide excellent correlation for identification of adenoviruses at the serotype level. [11][12][13][14] Each adenovirus serotype can be further discriminated into genome types on the basis of distinct DNA fragment patterns generated with restriction enzymes, and this type of analysis has been widely used in molecular epidemiologic studies.…”
Section: Introductionmentioning
confidence: 99%